Introduction: The Rise of Education Marketization and the Enduring Enigma of School Segregation - Yoon, Ee-Seul; Lubienski, Christopher (International Journal of Education Policy and Leadership, 2025)
The problem of school segregation has garnered considerable attention due to its adverse effects on learning opportunities and outcomes throughout the history of mass education, and increasingly in the marketized and privatized education landscapes worldwide. In this introductory article to the special issue of the International Journal of Education Policy & Leadership (IJEPL), “The Rise of Education Marketization and the Enduring Enigma of School Segregation,” we provide a brief overview of the articles included in this issue, as well as four major aspects of school segregation in the marketization of education. In doing so, we engage with existing theories of school segregation while marketization of education and school segregation.